A Research Itinerary from Fieldwork to Archives: Cape Town (South Africa), Festivals, Music, ‘Identities,’ Politics - (:unkn) unknown (My University, 2021)
For more than twenty years (from 1992 till 2015) I did research on the New Year Festivals which are organized at the beginning of every year in Cape Town (South Africa). These festivals include three series of competitions: between carnival troupes named Klopse (from the English clubs), between male choirs called Singkoore or Malay Choirs and between Christian brass bands known as Christmas Choirs or Christmas Bands. In the course of this research, I conducted a great number of interviews, videoed and photographed the festivals and their preparations, collected many printed documents on which I based several articles, book chapters and books (in English and in French); I also recorded a CD with a local choir singing for the Klopse as well as for the Singkoore and produced a video documentary on the 1994 edition of the festival. In this paper I explain the conditions in which I conducted this research, underlining the importance of the partnership I entered into with major actors of the festivals, and signal the implications of such partnerships. I also discuss the conditions in which my documentation was assembled and why most of it was deposited with a South African musical archive.
Keywords: African Research